Value‐adding in biosecurity surveillance and monitoring: Testing colour and non‐target semiochemical lures on Psylloidea and Pentatomoidea. (13th September 2022) - Moir, Melinda L.; Croeser, Louise; Telfer, Don; Fenner, Christopher; McCauley, Rosalie
Abstract: Cost efficiency in biosecurity surveillance is vital, and the ability to survey multiple pest species using just one trap is, therefore, highly appealing. The Psylloidea, or plantlice, contain significant horticultural pest species that act as vectors for a number of deleterious plant bacteria. We examine the efficacy of using two different coloured sticky traps, and two semiochemical lures on the general Psylloidea and Pentatomoidea fauna, and a target extant pest psyllid; tomato potato psyllid (TPP) Bactericera cockerelli (Šulc) in Western Australia. Specifically, we test the effect of semiochemical lure (no lure, Asian citrus psyllid ACP lure, brown marmorated stink bug BMSB lure, combined lures), sticky trap colour (yellow‐green vs yellow) and sentinel plant (tomato vs citrus) on psyllid and pentatomid species in 104 urban backyards across Perth, Australia. We found that tomato sentinel host plants and yellow‐green traps significantly increased the capture rate of TPP, but that lures decreased the capture of TPP constraining their use. Yellow‐green traps also increased the capture rate of all other Psylloidea. Although BMSB lures reduced TPP capture, these lures increased the abundances of other Psylloidea and the pest stinkbug Plautia affinis (Dallas) on traps. Thus, our experiment demonstrates that increased efficiencies can be gained with multi‐species traps and semiochemical lures for particular groups, provided that they have been tested on focal organisms in the first instance, as reactions to non‐target lures are unpredictable and species specific.